Investigating the Central Place Theory: A Case Study on Uzbekistan - Fakriyor Jamoliddinov; Jacinta Dsilva (Research Synergy Foundation, 2019)
Economic Geography is a sub-branch of geography that deals with issues such as the location, place, economic activities, human activities, and how these factors are interlinked to help understand the distribution of organizations and activities. This field can be further broken down to evaluate the factors on an individual level. Space or location analysis is where local growth models are treated as an economic resource that provides a strategic advantage for the firms located in them. Therefore, it is trivial to emphasize the importance of location for economic activity; however, only recently, it has been given due considerations by economic theory. The purpose of this study is to evaluate how the physical dimensions of Uzbekistan have improved the economy in recent times compared to the Soviet era and to investigate the central place theory about Mahallas. The methodology utilized for this paper was country-specific research and existing studies on space and location analysis. The paper also focuses on evaluating the renowned Central Place theory by Walter Christaller and its application using Uzbekistan as a case. This is a conceptual paper; therefore, literature review and recommendations based on previous studies will be the prime methodology. The findings based on extensive research confirm that there has been incremental growth in space and location analysis. It was also found that Uzbekistan has successfully utilized its space and territories for economic development. Also, the Central Place theory was applied in an interesting manner to Mahallas in Uzbekistan. Finally, the paper also highlights the importance of technological advancement and transportation to the success of economic development. This study follows a conceptual approach. Therefore, the limitation is to utilize the theories conducted by other researchers and apply them to Uzbekistan. Another practical limitation is that the researchers should have extensive knowledge about the country-specific in this case, Uzbekistan. Future studies can be done on conducting quantitative research using some of the empirical models from economic geography. This research paper contributes to the existing body of research on locational analysis and regional studies as well as economic development. There has been limited research conducted on economic development of Uzbekistan; a growing economy post-soviet era, and therefore, it is important to evaluate the significant contribution.